Antibodies to Macromolecular Platelet Factor 4-Heparin Complexes in Heparin-induced Thrombocytopenia: a Study of 44 Cases - Amiral, J; Bridey, F; Wolf, M; Boyer-Neumann, C; Fressinaud, E; Vissac, A M; Peynaud-Debayle, E; Dreyfus, M; Meyer, D (Thrombosis and Haemostasis, 1995)
As heparin-PF4 (H-PF4) complexes are the target for antibodies associated to heparin-induced thrombocytopenia (HIT), an ELISA has been developed and optimised for testing antibodies binding to H-PF4. This test was consistently negative in 50 healthy subjects (A492 <0.3) and 35 patients with other causes of thrombocytopenia (A492 <0.5). In contrast, 43 out of 44 HIT patients showed antibodies to H-PF4 (A492 = 1.70 ± 0.81) including 5 patients with a negative platelet aggregation test. In one patient with HIT, antibodies to H-PF4 were already present at day 7, whereas platelet counts dropped ≤ 100 × 109/l only at days 11–12. Surprisingly, among 41 patients under heparin for >7 days, 5 showed antibodies to H-PF4, without HIT. These findings underline the major interest of this ELISA for the early diagnosis of HIT. We also showed that LMWH as well as other sulphated polysaccharides can bind to HIT antibodies in the presence of PF4 and that their reactivity is dependent on the molecular weight and the sulphation grade. The mechanism for HIT involves platelet PF4 receptors which bind the macromolecular H-PF4 complexes formed in the presence of a well defined heparin/PF4 ratio.